Digitization of Library Archives as a Tool for Preservation of Cultural Heritage - Karekar, Shobha U.; Mudhol, Mahesh V. (Journal of Information and Knowledge, 2014)
Museums, libraries and archives play a vital role in encouraging everyone to carry on learning throughout their lives and make important contributions to establishing healthier and happier communities. Archives, perhaps the best kept lifelong secret of all, are amazing treasure troves that contain the collective memories of the nation. They provide glimpses into the past that help to make sense of the present and the future.1 The main aim of this paper is to understand the importance of archives and the necessity of preserving them for the future generation to come through the process of digitization. A questionnaire based survey was conducted at Krishnadas Shama Central Library, Panaji, Goa. Since this is a public library respondents belonged to all walks of life, such as students, people who do the research and people who just browse the archives out of interest. After the investigation it was found that digitization of archives made the users to do references with greater speed and most of the respondents have expressed their satisfaction for the benefits of digitization of archives.